Adipocytes containing adipokines causes β-cell regeneration in previously streptozotocin induced hyperglycemic rats model - Azahari, Nuraniza; Mohd Shukri, Nor Azwani; Khattak, Muhammad Muzaffar Ali Khan (MedCrave, 2020)
Introduction:The aim of this study was to evaluate the effect protein containing adiponectin from the adipocytes on the regeneration of pancreatic β-cells in rates previously treated with (STZ). Therefore, adipocytes from different sources were extracted for protein (adipokines) and the effect was evaluated on pancreatic β-cell regeneration. Methods: The protein extracts from trimmed off abdominal adipose tissues of meat sources, namely chicken, beef and lamb, were used in the present study. The fats were removed, and protein were isolated, and hydrolysate were prepared and injected to rats. The rats were induced hyperglycemia with streptozotocin (STZ) were divided into normal rats (Group-A), insulin treated rats (Group-B), protein containing beef adiponectin (PCBA) (Group-C), protein containing lamb adiponectin (PCLA) (Group-D), protein containing chicken adiponectin (PCCA) (Group-E) and no treatment hyperglycemic rats (Group-F). The rats were injected 30mg of the aforementioned proteins and pancreatic morphology was assessed two weeks post-treatment. Results: The pancreas of the Group-A showed normal islets of Langerhans with abundant beta cells. In the no treatment rats (Group-F), islets were lower in cellular density compared to the control and treatment groups. The pancreas of Group-C, D and E rats showed islets and acinar cells that were comparable to the control. The pancreas of insulin-treated Group-B was similar in architecture to the control group. Conclusions:The present study indicates that protein extracts containing adipokines from Adipocytes Containing Adiponectin Causes β-cell Regeneration in Rats